Housing Markets during the Rural-Urban Transition: Evidence from early 20th Century Spain - Juan Carmona Pidal; Markus Lampe; Joan Ramón Rosés (European Historical Economics Society (EHES), 2012)
This paper discusses how Spain's urban housing markets reacted to the far-reaching changes that affected the demand for dwellings during the first phase of the ruralurban transition process. To this end, we construct a new hedonic index of real housing prices and assemble a cross-regional panel dataset of price fundamentals. The results of our econometric analysis suggest that urban housing markets did not face supply constraints and responded swiftly to the growing demand for accommodation. In light of this new evidence, we conclude that housing markets were not a burden for Spanish economic development and that Spain's urban infrastructure and institutional framework and were suitable for the housing needs at the time.
Keywords: N93; N94; R30; 330; Hedonic prices; Demand and Supply of Housing; Regulation in Housing Markets